Sebaran spesies dan status kerapatan ekosistem mangrove di pesisir Kabupaten Muna Barat, Sulawesi Tenggara - Rahman Rahman; Yusli Wardiatno; Fredinan Yulianda; Iman Rusmana (Graduate School Bogor Agricultural University (SPs IPB), 2020)
Mangrove ecosystem is valuable coastal ecosystems for human because its economic, physical and ecological functions. One of the coastal areas which is the habitat of the mangove ecosystem is the coast of West Muna Regency. The coastal development in the coastal area had reduced the mangrove area and the density of mangrove ecosystem, which in turn affected the structure and density status of the ecosystem. The number of mangrove species in the coast of West Muna Regency was ten species consisting of Bruguiera cylindrica, Bruguiera gymnorrhiza, Rhizophora mucronata, Rhizophora apiculata, Rhizophora stylosa, Sonneratia alba, Xylocarpus granatum, Ceriops tagal, Scyphiphora hydrophyllacea, and Calophyllum inophyllum. The total density of mangrove was 752 trees/ha, however, by seeing in detail through each sampling station the density of Station I, II, III and IV was 879, 621, 687 and 820 trees/ha, respectively. Those densities are categorized as low density.